2020
DOI: 10.1183/23120541.00054-2020
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variation in forced vital capacity in patients with fibrotic interstitial lung disease using home spirometry

Abstract: Forced vital capacity (FVC) is used as the routine physiological measure to assess disease progression in fibrotic interstitial lung diseases (f-ILDs) [1]. New drugs are currently being investigated on top of "standard care" with antifibrotic drugs in idiopathic pulmonary fibrosis (IPF) and other f-ILD, resulting in small margins of change in FVC [2, 3]. Recently, the first trial of antifibrotic medication in patients with systemic sclerosis-associated interstitial lung disease has shown a numerically small bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 9 publications
2
15
0
Order By: Relevance
“…Within-subject variability in FVC measurements taken day-to-day or week-to-week has been observed in healthy individuals [ 17 ] as well as in subjects with IPF [ 4 , 6 ]. The literature is inconsistent with respect to diurnal variations in FVC; several studies have found FVC to be generally higher in the morning than in the afternoon [ 18 – 20 ], but this has not been observed in all studies [ 21 ]. In the INMARK trial, subjects were asked to perform spirometry in the morning, but fewer than a third of subjects adhered to this request.…”
Section: Discussionmentioning
confidence: 99%
“…Within-subject variability in FVC measurements taken day-to-day or week-to-week has been observed in healthy individuals [ 17 ] as well as in subjects with IPF [ 4 , 6 ]. The literature is inconsistent with respect to diurnal variations in FVC; several studies have found FVC to be generally higher in the morning than in the afternoon [ 18 – 20 ], but this has not been observed in all studies [ 21 ]. In the INMARK trial, subjects were asked to perform spirometry in the morning, but fewer than a third of subjects adhered to this request.…”
Section: Discussionmentioning
confidence: 99%
“…This high variability was probably caused by a lack of good instruction regarding home spirometry, adherence problems and technical problems with the hand-held spirometers [ 21 ]. The online home monitoring program used in the current study yielded similar results in IPF, sarcoidosis and other forms of pulmonary fibrosis, with a low variability in home-based FVC and a small number of technical issues and missing data [ 12–14 , 16 ]. Hence we believe that most issues raised in previous studies can be addressed by the use of an online system with direct data transmission to the hospital, low-threshold communication, e-mail reminders and feedback on the quality of the measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Half of the patients started with weekly home spirometry and the other 50% of patients started with daily home spirometry. Patients were instructed to perform spirometry at approximately the same time every day to reduce variability [ 16 ]. Measurements were sent directly to the hospital via an encrypted connection.…”
Section: Methodsmentioning
confidence: 99%
“…A handheld spirometer (Spirobank Smart, MIR, Italy) will be handed out to all patients. Patients will be instructed to undertake spirometry (three consecutive measurements) once a week at the same day, at approximately the same time to enhance compliance and reduce variability [ 23 ]. The best result of the day will be transmitted real-time to the patients’ personal platform and will be directly accessible for both patients and the study team.…”
Section: Methodsmentioning
confidence: 99%